1997
DOI: 10.1111/1467-9868.00070
|View full text |Cite
|
Sign up to set email alerts
|

Updating Schemes, Correlation Structure, Blocking and Parameterization for the Gibbs Sampler

Abstract: In this paper many convergence issues concerning the implementation of the Gibbs sampler are investigated. Exact computable rates of convergence for Gaussian target distributions are obtained. Different random and non-random updating strategies and blocking combinations are compared using the rates. The effect of dimensionality and correlation structure on the convergence rates are studied. Some examples are considered to demonstrate the results. For a Gaussian image analysis problem several updating strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
267
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(280 citation statements)
references
References 23 publications
8
267
0
5
Order By: Relevance
“…Concurrent with the increased application of MCMC sampling schemes to non-Gaussian state space models, has been the revelation that substantial improvements in the simulation efficiency of MCMC schemes, in a variety of contexts, can sometimes be obtained though simple model reparameterisation. Relevant work includes Gelfand, Sahu and Carlin (1995), Roberts and Sahu (1997), Pitt and Shephard (1999) Bos and Shephard (2006). This paper contributes to the literature by examining the effect of particular types of reparameterisation in two specific non-Gaussian state space models.…”
Section: Introductionmentioning
confidence: 98%
“…Concurrent with the increased application of MCMC sampling schemes to non-Gaussian state space models, has been the revelation that substantial improvements in the simulation efficiency of MCMC schemes, in a variety of contexts, can sometimes be obtained though simple model reparameterisation. Relevant work includes Gelfand, Sahu and Carlin (1995), Roberts and Sahu (1997), Pitt and Shephard (1999) Bos and Shephard (2006). This paper contributes to the literature by examining the effect of particular types of reparameterisation in two specific non-Gaussian state space models.…”
Section: Introductionmentioning
confidence: 98%
“…[17,37]). Joint updating of parameters is known to improve mixing in hierarchical models [28,29,33]. Along this line, Sorensen et al [37] suggested sampling the thresholds and the liabilities jointly to improve the mixing of thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of using a blocked sampler is that we only need one random draw to sample both the perspective indicator x i and the topic indicator z i , reducing the computational burden. Blocking a Gibbs sampler can also improve mixing of the MCMC chain, although this is not true in general (Roberts & Sahu 1997). The sampler has been implemented in C++/R and has been open sourced as an R package that can be found at https: //github.com/MansMeg/PerspectiveTopicModel.…”
Section: A Model Detailsmentioning
confidence: 99%